Formation of fully equiaxed grain microstructure in additively manufactured AlCoCrFeNiTi0.5 high entropy alloy. (15th December 2019) - Guan, S.; Solberg, K.; Wan, D.; Berto, F.; Welo, T.; Yue, T.M.; Chan, K.C.
Abstract: In this work, the non-equiatomic high entropy alloy AlCoCrFeNiTi0.5 was additively manufactured via the laser engineered net shaping (LENS™) process. Contrary to the columnar grain microstructure commonly observed in previously reported alloys, the as-deposited AlCoCrFeNiTi0.5 specimens exhibit a fully equiaxed grain microstructure in a wide range of temperature gradients G (85 to 1005 K/mm) and solidification velocities V (5 to 20 mm/s). The main microstructural characteristics were found to be B2-structured proeutectic dendrites delineated by lamellar or rod-like B2/A2 eutectic structures. The formation of this microstructural feature can be discussed with the aid of Scheil's solidification model. The proeutectic B2-structured dendrites were frequently found to be fragmented, which may provide profuse effective nucleation sites, and hence promote equiaxed grain formation. Furthermore, we estimated the volume fraction ϕ values of equiaxed crystals at solidification front for various G - V combinations established in this paper, which can provide a theoretical basis for our experimental findings. The current work provides guidelines for producing fully equiaxed alloys by the additive manufacturing (AM) process. Graphical abstract: Unlabelled Image Highlights: Fully equiaxed grain microstructures are easily achieved in additively manufactured high entropy alloy AlCoCrFeNiTi0.5 . The equiaxed grain formation is attributed to frequent dendrite fragmentation and hence profuse effective nucleation sites. A quantitative analysis is performed to provide a theoretical basis for our experimental findings.